Chitosan and water-soluble chitosan effects on refrigerated catfish fillet quality. (October 2019) - Bonilla, Franklin; Chouljenko, Alexander; Lin, Andy; Young, Britt M.; Goribidanur, Tanishq Sai; Blake, James C.; Bechtel, Peter J.; Sathivel, Subramaniam
Abstract: Chitosan's water insolubility restricts its use in some food systems. However, when treated with enzymes, a water-soluble chitosan is developed, which overcomes insolubility. The aim of this study was to evaluate the effect of chitosan and water-soluble chitosan applications on refrigerated catfish fillet quality. Fresh catfish fillets were separately vacuum tumbled with distilled water, 1% acetic acid, chitosan (0.5% in acetic acid), and water-soluble chitosan (0.5% in distilled water). Sampling was done at 0, 5, 10, 15, and 20 days. The fillets were analyzed for lipid oxidation, aerobic plate counts, yeast and mold counts, cutting force, color, and pH. Triplicate experiments were done and the data were statistically analyzed at a significance level of 0.05. Water-soluble chitosan had 86 ± 2% water solubility compared to 1.9 ± 0.2% for chitosan. Fillets treated with water-soluble chitosan solution had lipid oxidation reduced by approximately 70% compared to untreated fillets during 20 days of refrigerated storage. Chitosan treated fillets showed the highest inhibition with aerobic plate, yeast and mold counts. Initially, fillets treated with acetic acid and chitosan solutions had a more rapid decrease in hardness than those vacuum tumbled with water-soluble chitosan and distilled water. Therefore, this study showed both the advantages and limitations of applying chitosan or water-soluble chitosan for preserving catfish fillet quality during refrigerated storage.